Зміст диспозитивності при встановленні заповідального відказу у спадковому праві України - Кухарєв, О. Є.; Kukharev, O. Y.; ORCID: http://orcid.org/0000-0003-2086-9179 (Слово Національної школи суддів України. - 2018. - № 1. - С. 28–36, 2018)
Стаття присвячена дослідженню змісту диспозитивності при встановленні заповідального відказу як спеціального заповідального розпорядження. Наголошується, що свобода заповіту у цій сфері не обмежується лише правом спадкодавця зробити заповідальний відказ. Заповідач наділений широкими можливостями стосовно предмету легату, що виражається у переданні у власність або за іншим речовим правом майнового права або речі, що входять або не входить до складу спадщини. Закон містить відкритий перелік тих прав та речей, що можуть складати предмет заповідального відказу. Крім того, виконання легату не обмежене строком дії спадкового правовідношення.

The article investigates the degree of legal freedom of an individual while establishing a testamentary gift (legate) as a special testamentary disposition. The paper validates the conclusion that the inheritance law dispositivity as to legate establishing encompass: 1. Testator’s right to make a testamentary gift. 2. Non-exhaustive list of property rights or belongings, which can constitute a legate subject. 3. Expansion of testamentary gift subject is realised according to transfer into ownership or right in rem of a property right or belongings, included or not into estate. 4. Legal freedom as to time limit performance of a testamentary gift which can be beyond legal relationships, for example, when providing the right to liferent of housing. While performing a testamentary gift, the general provisions on obligation fulfillment must be applied taking into account the compulsory nature of the correspondent legal relationship and the specific nature of legatary relationship. First of all, it concerns the claims priority of the testator’s creditors over the claims of a legatee. Analysing the parties of legatary legal relationship, the author notes the possibility of legate establishing in favor of a person conceived during a testator’s life and born after his death by analogy with an heir. At the same time, the testamentary gift can not be made in favor of an heir by devise, as in this case the heir status absorbs the legatee status and in this connection the heir’s share will increase due to testamentary gift. In this case, the heir and the legatee have different legal status and are separate subjects of inheritance legal relationships. The current legislation attributes testamentary gift to the rights inseparably connected with a bearer’s identity. As a result, a legate can not be alienated, inherited and it is terminated by a legatee death.

Статья посвящена исследованию содержанию диспозитивности при установлении завещательного отказа как специального завещательного распоряжения. Отмечается, что свобода завещания в этой сфере не ограничивается лишь правом наследодателя сделать завещательный отказ. Завещатель наделен широкими возможностями относительно предмета легата, охватываемом передачу в собственность или по другому вещному праву имущественного права или вещи, которые входят или не входят в состав наследства. Закон содержит открытый перечень прав и вещей, составляющих предмет завещательного отказа. Кроме того, исполнение легата не ограничено сроком действия наследственного правоотношения.
Содержание диспозитивности при установлении завещательного отказа в наследственном праве Украины
The dispositivity essence while establishing testamentary gift in the inheritance law of Ukraine
Кухарєв, О. Зміст диспозитивності при встановленні заповідального відказу у спадковому праві України / Олександр Кухарєв // Слово Національної школи суддів України. - 2018. - № 1. - С. 28–36.
Keywords: Цивільне право. Civil Law. Гражданское право; Спадкове право. Inheritance law. Наследственное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; спадкування; заповіт; заповідальний відказ; заповідач; спадкоємець; відказоодержувач; легат; наследование; завещание; завещательный отказ; завещатель; наследник; отказополучатель; succession; will; testamentary gift; testator; heirs; legate; legatee